Counting protein molecules using quantitative fluorescence microscopy - Coffman, Valerie C. (2012)
In recent years, quantification of absolute protein numbers in cellular structures using fluorescence microscopy has become a reality. Two popular methods are available to a broad range of researchers with minimal equipment and analysis requirements: stepwise photobleaching to count discrete changes in intensity from a small number of fluorescent fusion proteins, and comparing the fluorescence intensity of a protein to a known in vivo or in vitro standard. This review summarizes the advantages and disadvantages of each method, and gives recent examples of each that answer important questions in their respective fields. We also highlight new counting methods that could become widely available in the future.